Fístulas intestinales en el Servicio de Cirugía del Hospital del Salvador. Casuística - Cárdenas S., Patricio; Ríos V., Marco; Troncoso O., Ekaterina; Cárdenas D., Rocío (Revista Hospital Clínico Universidad de Chile, 2010)
A study of patients with intestinal fístulas treated at the surgical clinic of the Hospital Salvador, Santiago de Chile, from January 2007 until June 2009. The sizes of the study were 26 patients in whom diagnosis was clinical and / or images and / or surgical condition. The average age at presentation was 54.8 years, of similar frequency in men and women (54% and 46% respectively). Postoperative fístulas occurred in 80% and 20% spontaneous. Postoperative fístulas were found in an early stage in 57% of cases (before 72 h postoperative). Predominance of high-flow fístulas (73%) and location in the small intestine 58% to 42% in colon. Surgical closure was performedin 52% of patients, spontaneous closure by 32% and 16% non-locking. 61.5% of patients experienced complications being the most frequent infectious cause. 54% of cases required nutritional support with total parenteral nutrition. In our study mortality was 15.3%.